1992
DOI: 10.1111/j.1365-2621.1992.tb06838.x
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Compounds of Beef Broth as Affected by Cooking Temperature

Abstract: Of various cooking temperatures studied, broth from beef obtained on heating at 85°C for 60 min had the most intense brothy flavor. The components of the fractions with brothy flavor were isolated by gel filtration chromatography and characterized. A significant correlation between cooking temperature of the broth and the concentration of certain compounds such as free amino acids (FAA) (r=0.88, p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
4
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 28 publications
5
29
4
1
Order By: Relevance
“…However, it is accepted that a range of different amino acids are required [13,17,[31][32][33], although it is not certain which of these play a primordial role in the development of this sensory characteristic. Several authors have reported an important role for different amino acids such as Ala, lysine (Lys), threonine (Thr) [31], Gly, methionine (Met), Phe and Tyr [14,18,34] in the generation of beef broth flavour, and Warendorf and Belitz [33] added hydroxyproline (Hpr) and taurine (Tau) to this list as producers of serum-like flavours.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is accepted that a range of different amino acids are required [13,17,[31][32][33], although it is not certain which of these play a primordial role in the development of this sensory characteristic. Several authors have reported an important role for different amino acids such as Ala, lysine (Lys), threonine (Thr) [31], Gly, methionine (Met), Phe and Tyr [14,18,34] in the generation of beef broth flavour, and Warendorf and Belitz [33] added hydroxyproline (Hpr) and taurine (Tau) to this list as producers of serum-like flavours.…”
Section: Resultsmentioning
confidence: 99%
“…However, in this category, like category D (beef broth flavour with non-characteristic astringent, warmed-over flavours), a large number of FAAs were present at concentrations significantly lower than mean values. Although a number of FAAs are known to participate in beef broth flavour [17,[31][32][33] it is not yet clear which of these are the most important. From the results of this study, one can deduce that at least concentrations of Arg, Thr, Ile, Val, Pro, Ser and M-His are not of crucial importance since these FAAs were present in concentrations significantly lower than mean values in all the broths in categories D and E (P~0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…최근에 건강지향적인 고기 생산 의 목적과 감귤부산물을 효율적으로 처리하고 활용하기 위 하여 돼지사료 [29]와 한우사료 [11]에 이를 첨가하여 급여하 는 연구가 이루어졌다. 감귤부산물에 함유된 hesperidin과 naringin [3,22] 등은 항산화 작용 [30], 세포증식 억제 [16], 지 질산화 예방 [9], 항돌연변이 활성 [7] Vit.E, 15,000 IU; Vit.K, 2,000 mg; Vit.B1, 15,000 mg; Vit.B2, 4,000 mg; Vit.B6, 3,000 mg; Vit.B12, 3,000 µg; Niacine 25,000 mg; Folic acid, 5,000 mg; Biotin, 12,000 mg; Pantothenic acid, 10,000 mg; Antioxidation, 6,000 mg 2) Contained per kg; Zn, 75,000 mg; Mn, 75,000 mg; Fe, 75,000 mg; Cu, 7,500 mg; I, 1,650mg; Se, 450 mg; S, 125,000 mg; Co, 150 mg The same as in Table 2.…”
Section: 서 론unclassified
“…Since the mixture of wheat flour and butter contains carbohydrate, protein and lipid as the main constituents, it is reasonable to assume that it would generate a characteristic flavor from the Maillard reaction during cooking. There are many reports on heated flavor, including model systems of the Maillard reaction (Shieberle & Hofmann, 1996;Bruechert et al, 1988;Cambero et al, 1992), but there has been little work on samples prepared by these actual cooking conditions, apart from work by the authors. Previous reports have described that many aroma components have been identified in brown roux heated to 160-180˚C by GC and GC-MS (Kato, 1993;Kato, 2001), but in roux samples heated to the range of 100˚C-140˚C (Kato, 1992;Kato, 1996), several components remained to be identified or confirmed.…”
mentioning
confidence: 99%